Effect of training duration and exercise on blood-borne substrates, plasma lactate and enzyme concentrations in Andalusian, Anglo-Arabian and Arabian breeds - Muñoz, A.; Riber, C.; Santisteban, R.; Gómez Lucas, Raquel; Castejón, F M (My University, 2024)
Metabolic responses to exercise differ between Andalusian horses and other breeds, although changes in plasma muscle enzymes have not been reported and most useful information is obtained from animals subjected to different training programmes. The objectives of this study were to 1) describe the changes in plasma enzymes during exercise in different horse breeds in relation to other biochemical parameters (Experiment A) and 2) assess the effect of training duration on these measures (Experiment B). Twenty stallions, 9 Andalusian (AN), 7 Arabian (A) and 4 Anglo-Arabian (AA), age 5-10 years, were studied. They performed 3 exercise tests (ET), consisting of a warm-up of 800 m at 0.7 km/h and 4 workloads at 15, 20, 25 and 30 km/h, at respective distances of 1250, 1670, 2080 and 2500 m, with 5 min active recovery between each workload (Experiment A). Three ETs were performed at the beginning and after 2 and 6 months of training (Experiment B). Venous blood samples were collected during the ETs and plasma glucose (GLU), free fatty acids (FFA), lactate (LA), creatine kinase (CK), lactate dehydrogenase (LDH), alpha-hydroxybutyrate dehydrogenase (HBHD), aspartate aminotransferase (AST), Na+, K+ and Cl- were measured. AN horses responded to exercise with greater increases in GLU, HBHD, LDH, CK and AST compared to the other breeds. An unexpected result in Experiment A was the lack of interbreed differences in plasma peak LA concentrations, since it is commonly accepted that AA and A horses have greater athletic potential. Although the glycolytic response to exercise was reduced after 2 months of training in the AA and A horses, and after 6 months of training in the AN horses, at the end of Experiment B, AN horses produced more lactate than the other 2 breeds. Most of the adaptations linked to training were found in the AN breed. The more striking changes in plasma enzyme activities corresponded to CK in AN horses after 2 months of training. The attenuation of CK response to exercise was related to lower extrafibrilar GLU utilisation with LA formation and greater fat metabolism. The results show that plasma muscle enzyme concentrations for the diagnosis of equine myopathies must be interpreted in relation to breed and training.